FRACTIONAL MATHEMATICAL MODEL FOR THE TRANSMISSION DYNAMICS AND CONTROL OF HEPATITIS C (FUDMA JOURNAL OF SCIENCES, 2024)
This study investigates various epidemiological aspects of Hepatitis C infection by employing a fractional-order mathematical model to evaluate the impact of treatment on the transmission dynamics of the disease. The research identifies conditions for the existence and uniqueness of the solution in the fractional-order case and conducts a stability analysis of the endemic equilibrium using the Lyapunov function method. Numerical simulations, performed using the fractional Adams–Bashforth–Moulton technique, demonstrate the effects of model parameters and fractional-order values on the control and spread of Hepatitis C. Further simulations with surface and contour plots reveal that higher contact rates and reduced treatment effectiveness lead to an increased prevalence of Hepatitis C. The study also concludes that optimizing treatment strategies can significantly decrease the disease's prevalence in the population.
Keywords: Hepatitis C; Fractional; Adam-Bashforth-Moulton; Transmission; Control; Strategies